Sulfonated modified CAU-1, mixed matrix membrane, preparation method and application

By sulfonating modified CAU-1, the problem of poor dispersion in polymeric matrix is ​​solved, and the CO2/N2 selectivity and permeability of the mixed matrix membrane are significantly improved, achieving more efficient CO2 separation performance.

CN119661861APending Publication Date: 2025-03-21GUANGDONG GAOCHUANG PARK TECHNOLOGY INCUBATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682031.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, CAU-1 has poor dispersion in polymeric matrix, which limits its application in mixed matrix membranes, resulting in poor CO2 separation performance.

Method used

By sulfonating modified CAU-1, negatively charged sulfonic acid groups are introduced to improve the dispersion and interface compatibility of fillers in the polymer matrix, thereby improving the permeability and selectivity of CO2.

Benefits of technology

The modified CAU-1 nanomaterials show significantly improved CO2/N2 selectivity and permeability in the mixed matrix membrane, breaking the trade-off effect in traditional membrane separation technology.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of gas separation membranes, and particularly discloses sulfonation modified CAU-1, a mixed matrix membrane, a preparation method and application. The preparation method of the mixed matrix membrane comprises the following steps: synthesizing CAU-1, and modifying sultone molecules to the surface of CAU-1 through ring-opening reaction to synthesize sulfonation modified CAU-1; and synthesizing the mixed matrix membrane doped with the sulfonated modified CAU-1 nano material. The method has the advantages that the raw materials are easy to obtain and low in price; the preparation process is simple, and industrialization is easy to realize; the prepared mixed matrix membrane is good in hydrophilicity and acid resistance; when the composite material is applied to the field of CO2 gas separation, the composite material has a relatively high CO2 permeability coefficient and a CO2 / N2 separation factor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas separation membranes, and in particular relates to a sulfonated modified CAU-1, a mixed matrix membrane, and a preparation method and application thereof. Background Art

[0002] Excessive carbon dioxide emissions will not only lead to environmental crises such as ocean acidification and greenhouse effect, but also affect human economic development. Carbon dioxide emissions cause global temperatures to rise, thus affecting labor production in industries such as agriculture, mining, and construction. The annual loss caused by the decline in labor productivity accounts for 2% of the global GDP. Effectively removing carbon dioxide produced by fossil fuel combustion and industrial production is essential to mitigate global warming and maintain a sustainable carbon-neutral society. So far, many gas separation technologies have been studied to capture CO2, namely pressure swing adsorption, hydration system, cryogenic distillation and membrane separation. Membrane separation technology has attracted more and more attention due to its advantages such as small size, high energy efficiency and low impact on the environment.

[0003] Mixed matrix membranes combine the advantages of inorganic membranes and polymer membranes. The amino carriers in the amino-containing polymer membranes can undergo a reversible chemical reaction with CO2, thereby promoting the transfer of CO2 in the membrane, showing good application prospects in CO2 separation. However, due to the regular chain segments and high crystallinity of the amino-containing polymers, the free volume of the prepared membrane is small and exhibits a high mass transfer resistance, which limits the effect of promoting the transfer of CO2 in the membrane. The dispersion and interfacial compatibility of suitable inorganic fillers in the polymer matrix have a great influence on the separation performance of mixed matrix membranes. Mixed matrix membranes with uniform inorganic fillers and good interfacial compatibility theoretically have better separation performance [Chemical communications 49 (2013) 8513-8515].

[0004] CAU-1 has excellent thermal stability and abundant amino and carboxyl functional groups. Its three-dimensional microporous framework has small triangular windows with a free pore size of 0.3-0.4 nm. The appropriate pore size is conducive to the separation of CO2. However, the poor dispersibility of nano-scale CAU-1 in the polymer matrix limits their application in mixed matrix membranes and increases the difficulty of membrane preparation [Chemical Engineering Science 189 (2018) 277-285]. The literature uses the hydrogen bonding between the amino group of CAU-1 and the carbonyl group in the PMMA polymer to prepare a dense and stable mixed matrix membrane. The prepared membrane has high H2 permeability and good H2 / CO2 selectivity [Chemical Communications 49 (2013) 8513-8515]. Xiao et al. used dodecyl aldehyde to modify the surface of CAU-1 to enhance its hydrophobicity, improve its dispersibility and inhibit its aggregation in trimethylol chloride (TMC) / n-hexane solution; however, the alkyl chain-modified CAU-1 lacked polar groups, which weakened the interaction between the filler and the polymer matrix [Water science and technology 86 (2022) 2642–2657]. Guo et al. covalently bonded polyethyleneimine (PEI) branched polymers to the outer surface of CAU-1 nanoparticles to improve the dispersibility of filler particles in solvents and polymer matrices; however, when using macromolecular polymers for modification, the molecular volume of PEI will increase after adsorbing CO2, and the volume expansion will more easily block the pores and increase the CO2 diffusion resistance, resulting in limited improvement in the separation performance of mixed matrix membranes [Chemical engineering science 189 (2018) 277-285]. Therefore, selecting a suitable modifier to modify CAU-1 is beneficial to improving the CO2 separation performance of mixed matrix membranes. Summary of the invention

[0005] The present invention aims to provide a preparation and application of a mixed matrix membrane doped with sulfonated modified CAU-1 nanomaterials. The purpose is to modify CAU-1 by sulfonation, and the negatively charged sulfonic acid groups on the surface of CAU-1 cause mutual repulsion, so that the filler is evenly dispersed in the polymer matrix. At the same time, the introduction of sulfonic acid groups is also conducive to improving the interface compatibility between the filler and the polymer matrix, and improving the permeability and selectivity of CO2 molecules in the membrane.

[0006] Based on this, the first aspect of the present invention provides a method for preparing sulfonated modified CAU-1, comprising the following steps:

[0007] The sultone is dissolved in solvent B to obtain solution C, wherein the mass concentration of the solution C is 100 g / L-200 g / L; CAU-1 is dispersed in solution C to obtain dispersion D, wherein the mass ratio of the CAU-1 to the sultone is 1:(1-10); the dispersion D is stirred at 10° C.-40° C. for 8 h-24 h to carry out a sulfonation modification reaction to obtain product E; the product E is centrifuged at a speed of 5000 rpm-10000 rpm for 3 min-20 min, then washed three times with dichloromethane and ethanol respectively, and then dried at 20° C.-80° C. for 12 h-48 h to obtain the sulfonated modified CAU-1.

[0008] In some embodiments, the preparation method of CAU-1 includes the following steps: dissolving aluminum chlorohexahydrate and 2-aminoterephthalic acid in a methanol solution to obtain a solution A, wherein the molar ratio of aluminum chlorohexahydrate to 2-aminoterephthalic acid is (2-4):1; the total mass concentration of aluminum chlorohexahydrate and 2-aminoterephthalic acid in the solution A is 30g / L-60g / L; reacting the solution A at 100°C-200°C for 12h-24h, then cooling to 25°C, centrifuging the product at 5000rpm-10000rpm for 3min-20min, then washing it three times with water, and drying it at 20°C-100°C for 12h-48h to obtain the CAU-1.

[0009] Wherein, the sultone is one of 1,3-propane sultone, 2,4-butane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, the solvent B is dichloromethane, methanol or acetone.

[0010] The second aspect of the present invention provides a sulfonated modified CAU-1 prepared by the above preparation method.

[0011] The third aspect of the present invention provides a mixed matrix membrane of doped sulfonated modified CAU-1 nanomaterials prepared from the sulfonated modified CAU-1.

[0012] The fourth aspect of the present invention provides a method for preparing the above-mentioned CAU-1 nanomaterial mixed matrix membrane doped with sulfonated modification, comprising the following steps:

[0013] The polymer matrix and the sulfonated modified CAU-1 are added to the membrane-forming solvent, and the casting solution is obtained after mixing. The casting solution is applied to the surface of the porous support by solution scraping method to prepare the doped sulfonated modified CAU-1 nanomaterial mixed matrix membrane.

[0014] In some preferred embodiments, the porous support is a hydrophilically modified porous support, and its preparation process is as follows: an aqueous solution of a hydrophilic modifier with a mass fraction of 0.05%-1% is used as solution F, and the solution F is scraped on the surface of the porous support, wherein the wet film thickness is 30μm-200μm, and dried at 25℃-60℃ and 30%-80% RH for 2h-4h to obtain the hydrophilically modified porous support.

[0015] In some preferred embodiments, the preparation process of the casting solution is as follows: dispersing the polymer matrix in water to obtain solution G, wherein the mass fraction of the polymer matrix in the solution G is 0.1%-5%; dispersing the sulfonated modified CAU-1 in the solution G to obtain dispersion H, wherein the mass ratio of the sulfonated modified CAU-1 to the polymer matrix is ​​(1-15):100; and then ultrasonically dispersing the dispersion H for 1h-24h to obtain the casting solution.

[0016] In some preferred embodiments, the porous support is one of polysulfone, polyethersulfone, polyvinylidene fluoride and polytetrafluoroethylene, with a molecular weight cutoff of 3000Da-60000 Da; the polymer matrix is ​​one of polyvinylamine (PVAm), polyethyleneimine (PEI), and chitosan (CS); the hydrophilic modifier is one of polyvinyl alcohol, polyethylene glycol, polypyrrolidone and polyethyleneimine, with a molecular weight of 200-50000.

[0017] The fifth aspect of the present invention provides an application of the above-mentioned CAU-1 nanomaterial mixed matrix membrane doped with sulfonated modified materials in the field of CO2 separation. Specifically, the mixed matrix membrane is used to separate CO2 / N2, and the gas permeability is tested by constant pressure variable volume method, and the purge gas is H2, and the purge gas flow rate is 10mL·min -1 -60mL·min -1 , the feed gas flow rate is 10 mL min -1 -100mL·min -1 The flow rates on the feed side and the permeate side were measured by flow meters, and the component content on the permeate side was measured by gas chromatography; the test temperature was 20°C-80°C, and the pressure difference was 0.1MPa-0.8MPa.

[0018] The beneficial effects of the present invention are:

[0019] (1) The sulfonic acid groups of sulfonated CAU-1 nanomaterials have an affinity for CO2 and can improve the permeability of gas separation membranes;

[0020] (2) Sulfonated modified CAU-1 improves the interfacial compatibility between the filler and the polymer matrix, making it uniformly dispersed in the polymer matrix;

[0021] (3) The sulfonated modified CAU-1 expands the hydrophilic region of the membrane and strengthens the facilitation of transport due to the introduction of the hydrophilic sulfonic acid group. At the same time, the introduced affinity sites and pore size cooperate with the PVAm chain to promote the transfer of CO2 and improve the gas selectivity.

[0022] (4) The preparation process of the nanomaterial and the membrane in the present invention is simple and controllable, the conditions are mild, and the operation is easy; the membrane preparation process is simple, which is conducive to industrialization;

[0023] (5) The prepared membrane was used to separate CO2 and N2. Experimental data showed that the permeability and selectivity of the mixed matrix membrane with sulfonated modified CAU-1 nanomaterials were greatly improved compared with the pure membrane, breaking the trade-off effect. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments to clearly and completely describe the concept and technical effects of the present invention so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0025] Comparative Example 1

[0026] A CAU-1 nanomaterial mixed matrix membrane, the preparation method of which comprises the following steps:

[0027] (1) Preparation of CAU-1: Aluminum chlorohydrate and 2-aminoterephthalic acid were dissolved in a methanol solution to prepare solution A, wherein the molar ratio of aluminum chlorohydrate to 2-aminoterephthalic acid was 2:1, and the total mass of aluminum chlorohydrate and 2-aminoterephthalic acid in the methanol solution was 31 g / L. Solution A was added to a high-pressure reactor, heated at 125°C for 18 hours, and then naturally cooled to 25°C. The product was centrifuged at a speed of 8000 rpm for 6 minutes, washed three times with deionized water, and then dried in a vacuum oven at 60°C for 24 hours to obtain a yellow solid product CAU-1.

[0028] (2) Preparation of CAU-1 nanomaterial mixed matrix membrane: The hydrophilic modifier polyvinyl alcohol was dissolved in deionized water to prepare solution B, wherein the mass fraction of polyvinyl alcohol in solution B was 0.1%. Solution B was scraped on the surface of the polysulfone support to a wet film thickness of 300 μm, and dried at 30°C, 40% RH for 4 h to obtain a hydrophilic modified polysulfone support. The polymer matrix polyvinylamine was dissolved in deionized water to prepare solution C, wherein the mass fraction of the polymer matrix in solution C was 0.5%. CAU-1 was dispersed in solution C to prepare dispersion D, wherein the mass ratio of CAU-1 to polyvinylamine was 7:100. Dispersion D was then ultrasonicated for 1 h and stirred for 2 h to obtain a casting solution. The casting solution was scraped on the surface of the hydrophilically modified polysulfone support to a wet film thickness of 50 μm, and dried at 30°C, 40% RH for 12 h to obtain a mixed matrix membrane.

[0029] The CO2 permeability coefficient of the prepared CAU-1 nanomaterial mixed matrix membrane was measured at a temperature of 25°C and a pressure difference of 0.1 MPa, and was 162 GPU (1 GPU = 10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 ), CO2 / N2 selectivity is 43.

[0030] Example 1

[0031] A mixed matrix membrane of doped sulfonated modified CAU-1 nanomaterials, the preparation method of which comprises the following steps:

[0032] (1) Preparation of CAU-1: Aluminum chlorohydrate and 2-aminoterephthalic acid were dissolved in a methanol solution to prepare solution A, wherein the molar ratio of aluminum chlorohydrate to 2-aminoterephthalic acid was 3:1, and the total mass of aluminum chlorohydrate and 2-aminoterephthalic acid in the methanol solution was 46 g / L. Solution A was added to a high-pressure reactor, heated at 125°C for 18 hours, and then naturally cooled to 25°C. The product was centrifuged at a speed of 8000 rpm for 5 minutes, washed three times with deionized water, and then dried in a vacuum oven at 80°C for 24 hours to obtain a yellow solid product CAU-1.

[0033] (2) Preparation of sulfonated modified CAU-1: Propylene-1,3-sultone was dissolved in dichloromethane to prepare solution B, where the ratio of propenyl-1,3-sultone in dichloromethane was 150 g / L. CAU-1 was dispersed in solution B to prepare dispersion C, where the mass ratio of CAU-1 to propenyl-1,3-sultone was 1:5. Dispersion C was stirred at 30°C for 24 hours to undergo sulfonation modification, thereby obtaining product D. Product D was centrifuged at a speed of 8000 rpm for 10 minutes, washed three times with dichloromethane and ethanol respectively, and then dried in a vacuum oven at 60°C for 24 hours to obtain sulfonated modified CAU-1.

[0034] (3) Preparation of sulfonated modified CAU-1 nanomaterial mixed matrix membrane: The hydrophilic modifier polyvinyl alcohol was dissolved in deionized water to prepare solution E, wherein the mass fraction of polyvinyl alcohol in solution E was 0.1%. Solution E was scraped on the surface of the polysulfone support to a wet film thickness of 30 μm, and dried at 30°C and 40% RH for 4 h to obtain a hydrophilic modified polysulfone support. The polymer matrix polyvinylamine was dissolved in deionized water to prepare solution F, wherein the mass fraction of polyvinylamine in solution F was 0.5%. The sulfonated modified CAU-1 was dispersed in solution F to prepare dispersion G, wherein the mass ratio of sulfonated modified CAU-1 to polyvinylamine was 7:100. Dispersion G was then ultrasonicated for 2 h and stirred for 2 h to obtain a casting solution. The casting solution was scraped on the surface of the hydrophilic modified polysulfone support to a wet film thickness of 50 μm, and dried at 30°C and 40% RH for 12 h to obtain a mixed matrix membrane.

[0035] The CO2 permeability coefficient of the prepared sulfonated modified CAU-1 nanomaterial mixed matrix membrane was measured at a temperature of 25°C and a pressure difference of 0.1 MPa, and was 500 GPU (1 GPU = 10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 ), CO2 / N2 selectivity is 67.

[0036] Example 2

[0037] A mixed matrix membrane of doped sulfonated modified CAU-1 nanomaterials, the preparation method of which comprises the following steps:

[0038] (1) Preparation of CAU-1: Aluminum chlorohydrate and 2-aminoterephthalic acid were dissolved in a methanol solution to prepare solution A, wherein the molar ratio of aluminum chlorohydrate to 2-aminoterephthalic acid was 4:1, and the total mass of aluminum chlorohydrate and 2-aminoterephthalic acid in the methanol solution was 60 g / L. Solution A was added to a high-pressure reactor, heated at 130°C for 12 hours, and then naturally cooled to 25°C. The product was centrifuged at a speed of 5000 rpm for 20 minutes, washed three times with deionized water, and then dried in a vacuum oven at 80°C for 12 hours to obtain a yellow solid product CAU-1.

[0039] (2) Preparation of sulfonated modified CAU-1: 1,3-propane sultone was dissolved in dichloromethane to prepare solution B, wherein the ratio of 1,3-propane sultone in dichloromethane was 150 g / L. CAU-1 was dispersed in solution B to prepare dispersion C, wherein the mass ratio of CAU-1 to propenyl-1,3-sultone was 1:2. Dispersion C was stirred at 25°C for 12 h to undergo sulfonation modification, thereby obtaining product D. Product D was centrifuged at a speed of 7000 rpm for 5 min, washed three times with dichloromethane and ethanol respectively, and then dried in a vacuum oven at 80°C for 12 h to obtain sulfonated modified CAU-1.

[0040] (3) Preparation of sulfonated modified CAU-1 nanomaterial mixed matrix membrane: The hydrophilic modifier polyethylene glycol was dissolved in deionized water to prepare solution E, wherein the mass fraction of polyethylene glycol in solution E was 0.2%. Solution E was scraped on the surface of the polysulfone support to a wet film thickness of 100 μm, and dried at 30°C, 50% RH for 6 h to obtain a hydrophilic modified polysulfone support. The polymer matrix polyvinylamine was dissolved in deionized water to prepare solution F, wherein the mass fraction of polyvinylamine in solution F was 0.5%. The sulfonated modified CAU-1 was dispersed in solution F to prepare dispersion G, wherein the mass ratio of sulfonated modified CAU-1 to polyvinylamine matrix was 3:100. Dispersion G was then ultrasonicated for 2 h and stirred for 2 h to obtain a casting solution. The casting solution was scraped on the surface of the hydrophilic modified polysulfone support to a wet film thickness of 80 μm, and dried at 30°C, 40% RH for 12 h to obtain a mixed matrix membrane.

[0041] The CO2 permeability coefficient of the prepared sulfonated modified CAU-1 nanomaterial mixed matrix membrane was measured at a temperature of 25°C and a pressure difference of 0.2 MPa, and was 371 GPU (1 GPU = 10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 ), CO2 / N2 selectivity is 45.

[0042] Example 3

[0043] A mixed matrix membrane of doped sulfonated modified CAU-1 nanomaterials, the preparation method of which comprises the following steps:

[0044] (1) Preparation of CAU-1: Aluminum chlorohydrate and 2-aminoterephthalic acid were dissolved in a methanol solution to prepare solution A, wherein the molar ratio of aluminum chlorohydrate to 2-aminoterephthalic acid was 2:1, and the total mass of aluminum chlorohydrate and 2-aminoterephthalic acid in the methanol solution was 30 g / L. Solution A was added to a high-pressure reactor, heated at 110°C for 14 hours, and then naturally cooled to 25°C. The product was centrifuged at a speed of 8000 rpm for 5 minutes, washed three times with deionized water, and dried in a vacuum oven at 60°C for 24 hours to obtain a yellow solid product CAU-1.

[0045] (2) Preparation of sulfonated modified CAU-1: Propylene-1,3-sultone was dissolved in dichloromethane to prepare solution B, wherein the ratio of propenyl-1,3-sultone in dichloromethane was 150 g / L. CAU-1 was dispersed in solution B to prepare dispersion C, wherein the mass ratio of CAU-1 to propenyl-1,3-sultone was 1:3. Dispersion C was stirred at 35°C for 24 hours to undergo sulfonation modification, thereby obtaining product D. Product D was centrifuged at a speed of 8500 rpm for 5 minutes, washed three times with dichloromethane and ethanol respectively, and then dried in a vacuum oven at 60°C for 24 hours to obtain sulfonated modified CAU-1.

[0046] (3) Preparation of sulfonated modified CAU-1 nanomaterial mixed matrix membrane: The hydrophilic modifier polyvinyl alcohol was dissolved in deionized water to prepare solution E, wherein the mass fraction of polyvinyl alcohol in solution E was 0.1%. Solution E was scraped on the surface of the polyethersulfone support to a wet film thickness of 50 μm, and dried at 30°C, 40% RH for 4 h to obtain a hydrophilic modified polyethersulfone support. The polymer matrix polyvinylamine was dissolved in deionized water to prepare solution F, wherein the mass fraction of polyvinylamine in solution G was 0.5%. The sulfonated modified CAU-1 was dispersed in solution F to prepare dispersion G, wherein the mass ratio of sulfonated modified CAU-1 to polyvinylamine was 5:100. Dispersion G was then ultrasonicated for 1 h and stirred for 2 h to obtain a casting solution. The casting solution was scraped on the surface of the hydrophilic modified polyethersulfone support to a wet film thickness of 50 μm, and dried at 30°C, 40% RH for 48 h to obtain a mixed matrix membrane.

[0047] The CO2 permeability coefficient of the prepared sulfonated modified CAU-1 nanomaterial mixed matrix membrane was measured at a temperature of 25°C and a pressure difference of 0.1 MPa, and was 438 GPU (1 GPU = 10 -6 cm 3(STP) cm -2 ·s -1 cmHg -1 ), CO2 / N2 selectivity is 57.

[0048] Example 4

[0049] A mixed matrix membrane of doped sulfonated modified CAU-1 nanomaterials, the preparation method of which comprises the following steps:

[0050] (1) Preparation of CAU-1: Aluminum chlorohydrate and 2-aminoterephthalic acid were dissolved in a methanol solution to prepare solution A, wherein the molar ratio of aluminum chlorohydrate to 2-aminoterephthalic acid was 3:1, and the total mass of aluminum chlorohydrate and 2-aminoterephthalic acid in the methanol solution was 46 g / L. Solution A was added to a high-pressure reactor, heated at 125°C for 24 hours, and then naturally cooled to 25°C. The product was centrifuged at a speed of 8000 rpm for 5 minutes, washed three times with deionized water, and then dried in a vacuum oven at 60°C for 24 hours to obtain a yellow solid product CAU-1.

[0051] (2) Preparation of sulfonated modified CAU-1: 2,4-butane sultone was dissolved in dichloromethane to prepare solution B, wherein the ratio of 2,4-butane sultone in methanol was 2 g / L. CAU-1 was dispersed in solution B to prepare dispersion C, wherein the mass ratio of CAU-1 to 2,4-butane sultone was 1:7. Dispersion C was stirred at 35°C for 24 hours to undergo sulfonation modification, thereby obtaining product D. Product D was centrifuged at a speed of 6000 rpm for 5 minutes, washed three times with dichloromethane and ethanol respectively, and then dried in a vacuum oven at 60°C for 24 hours to obtain sulfonated modified CAU-1.

[0052] (3) Preparation of sulfonated modified CAU-1 nanomaterial mixed matrix membrane: The hydrophilic modifier polypyrrolidone was dissolved in deionized water to prepare solution E, wherein the mass fraction of polyvinyl alcohol in solution F was 0.5%. Solution E was scraped on the surface of the polyvinylidene fluoride support to a wet film thickness of 60 μm, and dried at 30°C, 40% RH for 4 h to obtain a hydrophilic modified polyvinylidene fluoride support. The polymer matrix polyethyleneimine was dissolved in deionized water to prepare solution F, wherein the mass fraction of polyvinylamine in solution F was 1%. The sulfonated modified CAU-1 was dispersed in solution F to prepare dispersion G, wherein the mass ratio of sulfonated modified CAU-1 to polyvinylamine was 10:100. Dispersion G was then ultrasonicated for 2 h and stirred for 2 h to obtain a casting solution. The casting solution was scraped on the surface of the hydrophilic modified polyvinylidene fluoride support to a wet film thickness of 50 μm, and dried at 30°C, 40% RH for 12 h to obtain a mixed matrix membrane.

[0053] The CO2 permeability coefficient of the prepared sulfonated modified CAU-1 nanomaterial mixed matrix membrane was measured at a temperature of 25°C and a pressure difference of 0.1 MPa, and was 540 GPU (1 GPU = 10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 ), CO2 / N2 selectivity is 60.

[0054] Example 5

[0055] A mixed matrix membrane of doped sulfonated modified CAU-1 nanomaterials, the preparation method of which comprises the following steps:

[0056] (1) Preparation of CAU-1: Aluminum chlorohydrate and 2-aminoterephthalic acid were dissolved in a methanol solution to prepare solution A, wherein the molar ratio of aluminum chlorohydrate to 2-aminoterephthalic acid was 3:1, and the total mass of aluminum chlorohydrate and 2-aminoterephthalic acid in the methanol solution was 46 g / L. Solution A was added to a high-pressure reactor, heated at 125°C for 18 hours, and then naturally cooled to 25°C. The product was centrifuged at a speed of 8000 rpm for 5 minutes, washed three times with deionized water, and then dried in a vacuum oven at 60°C for 24 hours to obtain a yellow solid product CAU-1.

[0057] (2) Preparation of sulfonated modified CAU-1: 1,4-butane sultone was dissolved in dichloromethane to prepare solution B, and the ratio of propenyl-1,3-sultone in dichloromethane was 125 g / L. CAU-1 was dispersed in solution B to prepare dispersion C, wherein the mass ratio of CAU-1 to 1,4-butane sultone was 1:4. Dispersion C was stirred at 30°C for 24 hours to undergo sulfonation modification, and product D was obtained. Product D was centrifuged at a speed of 8000 rpm for 10 minutes, washed three times with dichloromethane and ethanol respectively, and then dried in a vacuum oven at 70°C for 24 hours to obtain sulfonated modified CAU-1.

[0058] (3) Preparation of sulfonated modified CAU-1 nanomaterial mixed matrix membrane: The hydrophilic modifier polyethyleneimine was dissolved in deionized water to prepare solution E, wherein the mass fraction of polyethyleneimine in solution E was 0.1%. Solution E was scraped on the surface of the polytetrafluoroethylene support to a wet film thickness of 80 μm, and dried at 30°C, 40% RH for 8 h to obtain a hydrophilic modified polytetrafluoroethylene support. The polymer matrix chitosan was dissolved in deionized water to prepare solution F, wherein the mass fraction of chitosan in solution F was 2%. The sulfonated modified CAU-1 was dispersed in solution F to prepare dispersion G, wherein the mass ratio of sulfonated modified CAU-1 to polyethyleneamine was 7:100. Dispersion G was then ultrasonicated for 3 h and stirred for 8 h to obtain a casting solution. The casting solution was scraped on the surface of the hydrophilic modified polytetrafluoroethylene support to a wet film thickness of 30 μm, and dried at 30°C, 40% RH for 12 h to obtain a mixed matrix membrane.

[0059] The CO2 permeability coefficient of the prepared sulfonated modified CAU-1 nanomaterial mixed matrix membrane was measured at a temperature of 25°C and a pressure difference of 0.1 MPa, and was 498 GPU (1 GPU = 10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 ), CO2 / N2 selectivity is 64.

[0060] Compared with Comparative Example 1, the CO2 / N2 selectivity of the mixed matrix membranes of CAU-1 nanomaterials doped with sulfonated modified materials prepared in Examples 1 to 5 was significantly improved. The introduced sulfonic acid groups can increase the solubility of CO2 in the membrane and accelerate the transfer of CO2 in the membrane.

[0061] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. A method for preparing sulfonated modified CAU-1, characterized in that: The following steps are involved: The sultone is dissolved in solvent B to obtain solution C, wherein the mass concentration of the solution C is 100 g / L-200 g / L; CAU-1 is dispersed in solution C to obtain dispersion D, wherein the mass ratio of the CAU-1 to the sultone is 1:(1-10); the dispersion D is stirred at 10° C.-40° C. for 8 h-24 h to carry out a sulfonation modification reaction to obtain product E; the product E is centrifuged at a speed of 5000 rpm-10000 rpm for 3 min-20 min, then washed three times with dichloromethane and ethanol respectively, and then dried at 20° C.-80° C. for 12 h-48 h to obtain the sulfonated modified CAU-1.

2. The preparation method according to claim 1, characterized in that: The preparation method of CAU-1 comprises the following steps: dissolving aluminum chlorohexahydrate and 2-aminoterephthalic acid in a methanol solution to obtain a solution A, wherein the molar ratio of aluminum chlorohexahydrate to 2-aminoterephthalic acid is (2-4):1; the total mass concentration of aluminum chlorohexahydrate and 2-aminoterephthalic acid in the solution A is 30 g / L-60 g / L; reacting the solution A at 100° C.-200° C. for 12 h-24 h, then cooling to 25° C., centrifuging the product at 5000 rpm-10000 rpm for 3 min-20 min, then washing with water three times, and drying at 20° C.-100° C. for 12 h-48 h to obtain the CAU-1.

3. The preparation method according to claim 1, characterized in that: The sultone is one of 1,3-propane sultone, 2,4-butane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or the solvent B is dichloromethane, methanol or acetone.

4. A sulfonated modified CAU-1, characterized in that: Prepared by the preparation method according to any one of claims 1 to 3.

5. A mixed matrix membrane of CAU-1 nanomaterials doped with sulfonate, characterized in that: It is prepared from the sulfonated modified CAU-1 described in claim 4.

6. A method for preparing a mixed matrix membrane of CAU-1 nanomaterials doped with sulfonated modified CAU-1, characterized in that: The following steps are involved: The polymer matrix and the sulfonated modified CAU-1 described in claim 4 are added to a membrane-forming solvent, mixed to obtain a casting solution, and the casting solution is applied to the surface of a porous support by a solution scraping method to prepare the doped sulfonated modified CAU-1 nanomaterial mixed matrix membrane.

7. The preparation method according to claim 6, characterized in that: The porous support is a hydrophilically modified porous support, and its preparation process is as follows: an aqueous solution of a hydrophilic modifier with a mass fraction of 0.05%-1% is used as solution F, and the solution F is scraped on the surface of the porous support, wherein the wet film thickness is 30μm-200μm, and dried at 25℃-60℃ and 30%-80% RH for 2h-4h to obtain the hydrophilically modified porous support.

8. The preparation method according to claim 7, characterized in that: The preparation process of the casting solution is as follows: the polymer matrix is ​​dispersed in water to obtain a solution G, wherein the mass fraction of the polymer matrix in the solution G is 0.1%-5%; the sulfonated modified CAU-1 is dispersed in the solution G to obtain a dispersion H, wherein the mass ratio of the sulfonated modified CAU-1 to the polymer matrix is ​​(1-15):100; and then the dispersion H is ultrasonically dispersed for 1h-24h to obtain the casting solution.

9. The preparation method according to claim 8, characterized in that: The porous support is one of polysulfone, polyethersulfone, polyvinylidene fluoride and polytetrafluoroethylene, with a molecular weight cutoff of 3000Da-60000 Da; and / or, the polymer matrix is ​​one of polyvinylamine (PVAm), polyethyleneimine (PEI), chitosan (CS); and / or, the hydrophilic modifier is one of polyvinyl alcohol, polyethylene glycol, polypyrrolidone and polyethyleneimine, with a molecular weight of 200-50000.

10. Use of the doped sulfonated modified CAU-1 nanomaterial mixed matrix membrane as claimed in claim 5 or the doped sulfonated modified CAU-1 nanomaterial mixed matrix membrane prepared by the preparation method according to any one of claims 6 to 9 in the field of CO2 separation.